Potato calcineurin B-like protein CBL4, interacting with calcineurin B-like protein-interacting protein kinase CIPK2, positively regulates plant resistance to stem canker caused by Rhizoctonia solani - Yang, Shuai; Li, Jie; Lu, Jie; Wang, Ling; Min, Fanxiang; Guo, Mei; Wei, Qi; Wang, Wenzhong; Dong, Xuezhi; Mao, Yanzhi; Hu, Linshuang; Wang, Xiaodan (Frontiers in Microbiology, 2023)
Calcium sensor calcineurin B-like proteins (CBLs) and their interacting partners, CBL-interacting protein kinases (CIPKs), have emerged as a complex network in response to abiotic and biotic stress perception. However, little is known about how CBL-CIPK complexes function in potatoes. In this study, we identified the components of one potato signaling complex, StCBL4–StCIPK2, and characterized its function in defense against Rhizoctonia solani causing stem canker in potato. Expressions of both StCBL4 and StCIPK2 from potato were coordinately induced upon R. solani infection and following exposure to the defense genes. Furthermore, transient overexpression of StCBL4 and StCIPK2 individually and synergistically increased the tolerance of potato plants to R. solani in Nicotiana benthamiana. Additionally, the transgenic potato has also been shown to enhance resistance significantly. In contrast, susceptibility to R. solani was exhibited in N. benthamiana following virus-induced gene silencing of NbCBL and NbCIPK2. Evidence revealed that StCBL4 could interact in yeast and in planta with StCIPK2. StCBL4 and StCIPK2 transcription was induced upon R. solani infection and this expression in response to the pathogen was enhanced in StCBL4- and StCIPK2- transgenic potato. Moreover, accumulated expression of pathogenesis-related (PR) genes and reactive oxygen species (ROS) was significantly upregulated and enhanced in both StCBL4- and StCIPK2- transgenic potato. Accordingly, StCBL4 and StCIPK2 were involved in regulating the immune response to defend the potato plant against R. solani. Together, our data demonstrate that StCBL4 functions in concert with StCIPK2, as positive regulators of immunity, contributing to combating stem canker disease in potato.